New Masters, New Servants: Migration, Development, and Women Workers in China - Mcquaide, Shiling (Labour / Le Travail, 2009)
The article reviews the book, "New Masters, New Servants: Migration, Development, and Women Workers in China," by Yan Hairong.
Keywords: BOOKS -- Reviews; CHINA -- Social conditions -- 1976-2000; NEW Masters, New Servants: Migration, Development & Women Workers in China (Book); Nonfiction; YAN Hairong